Karakteristik Tinggi Gelombang Laut di Perairan Halmahera Utara dan Morotai pada Periode Waktu ENSO Tahun 2012-2021 - Mudho, Hendrik Trio; Azies, Ibnu Abdul; Setiyadi, Johar; Kisnarti, Engki Andri; Pranowo, Widodo Setiyo (Universitas Diponegoro, 2025)
North Halmahera and Morotai are strategic regions in the North Maluku Islands, Indonesia, rich in marine biodiversity and with great potential in the maritime, trade, and fisheries sectors. These regions serve as crucial routes for maritime transportation and regional trade, making accurate information about the physical conditions of the sea, particularly wave height, essential for ensuring the safety and security of shipping lanes. This study aims to analyze the impact of the El-Nino Southern Oscillation (ENSO) phenomenon on ocean wave heights in the waters of North Halmahera and Morotai during the period from 2012 to 2021. Additionally, the study measures the correlation between the Southern Oscillation Index (SOI) and Significant Wave Height (SWH). The data used in this study include wave data from the Marine Copernicus platform and SOI data obtained from http://www.bom.gov.au/climate/enso/soi/. Three observation stations were selected in the waters of North Halmahera and Morotai to monitor changes and variations in SWH during the ENSO phenomenon. A correlation analysis was conducted to determine the relationship between SOI values and SWH at each observation station. The results indicate that during the El-Nino phase, wave heights decreased significantly at several stations, particularly at stations 1 and 3, with a negative correlation between SOI and SWH. Conversely, during the La-Nina phase, wave heights increased, especially at stations 2 and 3, showing a stronger positive correlation. The relationship between SOI and SWH varied depending on location and time period. This study concludes that ENSO has a significant impact on the variation in wave heights in the waters of North Halmahera and Morotai. These findings are important for supporting maritime safety and managing maritime activities in the region.